Prevalence and molecular epidemiology of Canine parvovirus 2 in diarrheic dogs in Colombia, South America: A possible new CPV-2a is emerging? (2023)
Since its identification in 1978, Canine parvovirus type 2 (CPV-2) has been considered a pathogen of great importance in the canine population because it causes severe enteritis with high mortality rates in pups. CPV-2 is a virus belonging to the family Parvoviridae. Currently, there are three described antigenic variants (CPV-2a, CPV-2b, and CPV-2c). CPV-2c is an emerging virus that is seen as a global health hazard. The objective of this work was to confirm the presence of CPV-2 in dogs with acute gastroenteritis compatible with parvovirus and to molecularly characterize the antigenic variants circulating in two regions of Colombia. An analytical cross-sectional study was conducted with fecal samples collected from 71 dogs showing signs of acute diarrhea. The samples were processed and polymerase chain reaction (PCR), restriction fragment length polymorphism analysis (RFLP), sequencing and phylogenetic analysis was performed to detect and characterize CPV. A total of 70.42% of the individuals were confirmed positive for CPV-2. Statistically differences were found in the presentation of CPV-2 between the evaluated regions. Phylogenetic analyses confirmed the presence of the antigenic variants CPV-2a/2b. Moreover, we found the presence of two conserved substitutions Asn428Asp and Ala514Ser in the VP2 protein suggesting the presence of a possible new CPV-2a variant circulating in Colombia. This study demonstrates the importance of the CPV 2a/2b in the region and highlights the importance of performing molecular studies for the early detection of new antigenic variants of CPV-2. © 2017 Elsevier B.V.